The Kraken Project [compact disc, unabridged] - Preston, Douglas J. (Preston, Douglas J. Wyman Ford series., 2014)
NASA is designing a probe-raft-which will be dropped into the Kraken Mare, the largest sea on Saturn's great moon Titan. There, it will embark on a journey of exploration. A NASA team led by Melissa Shepherd has developed "Dorothy," a powerful, self-modifying AI software program to operate the raft autonomously. As the probe is being tested an explosion kills seven scientists. The AI program in the raft, called 'Dorothy,' flees into the Internet. Former CIA agent Wyman Ford is tapped by the president's science advisor to track down the software with the help of Dorothy's creator, Melissa Shepherd. But they are not the only ones looking for Dorothy. Two Wall Street traders want to capture Dorothy's code and turn her into a high-speed trading bot. As the pursuit converges on a house in Northern California, Wyman must face the question: is rescuing Dorothy the right thing, or is the AI bent on wiping out the cancer that is humankind?